Jan Kuklík, René Petráš, Minorities and law in Czechoslovakia, 1918–1992, Karolinum Press, Prague 2017, pp. 302 - Gąsior, Grzegorz (Klio - Czasopismo Poświęcone Dziejom Polski i Powszechnym, 2021)
The reviewed monograph by Jan Kuklík and René Petráš entitled Minorities and law in Czechoslovakia, 1918–1992, Karolinum Press, Prague 2017, is dedicated to the legal situation of national minorities in Czechoslovakia in the years 1918–1992. Although it constitutes a useful guide to appropriate legislation, the authors show some tendency to emphasise the democratic features of state policy towards minorities in the interwar period and lessen the significance of some of its flaws